APPLICATION OF AI TO ENHANCE NETWORK PERFORMANCE & SECURITY - Rajesh P.Porwal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The rapid evolution of network infrastructure and the increasing sophistication of cyber threats have necessitated the development of intelligent solutions for network management and security. This paper examines the application of artificial intelligence (AI) techniques to enhance both network performance optimization and security mechanisms. We present a comprehensive analysis of machine learning algorithms, deep learning models, and AI-driven approaches that address critical challenges in modern networking environments. Our research demonstrates that AI-powered solutions can significantly improve network throughput, reduce latency, detect anomalies, and mitigate security threats in real-time. The paper reviews current methodologies, presents performance metrics, and discusses future directions for AI integration in network systems.